2016
DOI: 10.1021/acs.langmuir.6b01877
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Nonhomogeneous Structure of RAD51 Filaments Using Nanofluidic Channels

Abstract: RAD51 is the key component of the homologous recombination pathway in eukaryotic cells and performs its task by forming filaments on DNA. In this study we investigate the physical properties of RAD51 filaments formed on DNA using nanofluidic channels and fluorescence microscopy. Contrary to the bacterial ortholog RecA, RAD51 forms inhomogeneous filaments on long DNA in vitro, consisting of several protein patches. We demonstrate that a permanent "kink" in the filament is formed where two patches meet if the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…Efficient bridging also leads to local condensation of DNA along the sugar-phosphate backbone. The formation of circles with local compactions is unique for CtIP and was not observed with, e.g., RAD51, another hallmark HR protein that forms extended filaments in nanofluidic channels (42). Circularization by hybridization was previously observed for the NC chaperone from the HIV-1 virus, but no local compaction was detected (7).…”
Section: Discussionmentioning
confidence: 87%
“…Efficient bridging also leads to local condensation of DNA along the sugar-phosphate backbone. The formation of circles with local compactions is unique for CtIP and was not observed with, e.g., RAD51, another hallmark HR protein that forms extended filaments in nanofluidic channels (42). Circularization by hybridization was previously observed for the NC chaperone from the HIV-1 virus, but no local compaction was detected (7).…”
Section: Discussionmentioning
confidence: 87%
“…On the nanoscale, the persistent photostability of NV centers, together with the present rotational-motion sensing, will make nanodiamonds indispensable tools to investigate nanoscale fluid mechanics. The classical experimental tool to visualize nanofluids is organic-molecular fluorescent probes 46 , 47 that can also be used for fluorescence depolarization spectroscopy 48 . This method, however, suffers from bleaching of dyes and can only be used for a short period of time and in some specific conditions at specific pH and temperature range.…”
Section: Discussionmentioning
confidence: 99%
“…Because the lipid bilayer exhibited high capability to avoid nonspecific adsorption of proteins (Figure b,c), it enabled the rapid movement of protein–DNA complexes in the nanochannels (Figure d). Therefore, the lipid bilayer‐based coating is very useful to facilitate the direct visualization of the structure and the dynamics of protein–DNA complexes in nanochannels . Last but not the least, it is worthy of attention that more recently Kitamori and co‐workers demonstrated that the use of a nanochannel coated with a lipid bilayer allowed sampling of a single cell content, which has been a challenge in single cell analysis because of the ultrasmall volume.…”
Section: Nanofluidics With Functionalized Surfacesmentioning
confidence: 99%